Improved carbonate formation from ethanol oxidation on nickel supported Pt–Rh electrode in alkaline medium at room temperature. (19th October 2015) - Mukherjee, Parthasarathi; Roy, Partha Sarathi; Bhattacharya, Swapan Kumar
Abstract: In search for catalysts capable to oxidize small alcohols completely to CO3 2− in alkali, a few nickel supported platinum-rhodium (Pt–Rh) binary electrodes of varying mutual composition have been constructed by galvanostatic co-deposition of Pt–Rh on Ni support from suitable precursors' solutions. The co-deposited particles are found to lie in the nano-size domain by electron microscopy. Catalyst with approximately 35 atom% of Rh shows the highest electrocatalytic activity among the various compositions of the binary Ni/PtRh catalyst system studied for anodic oxidation of ethanol. Ex-situ FTIR studies show that molar ratio of the two products CO3 2− and CH3 COO − in sequence, is increased on increasing the content of Rh in the binary deposit. Extended studies of ethanol, acetaldehyde and acetate at low concentrations reveal that electrochemically produced M−OH is responsible for chemical oxidations of organic fuels and related intermediates. The results lead to develop a proposed mechanism for the reaction. Graphical abstract: Highlights: Increased C–C bond breaking ability of PtRh electrocatalyst Ca.35 atom% of Rh shows best electrocatalytic activity for ethanol oxidation. Ethanol is oxidized to carbonate through acetaldehyde and acetate intermediates. Proposed path of ethanol oxidation.